Determinan sosial ekonomi kesenjangan distribusi Pendapatan penduduk di Kawasan Timur Indonesia - Amaluddin, Amaluddin; Hanoeboen, Bin Raudha Arif; Ramly, Amin (Jurnal Paradigma Ekonomika, 2020)
Inequality of income distribution and its determinants still leaves mixed debate and empirical findings. The source of inequality in population income distribution is in Eastern Indonesia (KTI) in line with the economic development performance that is still low compared to Western Indonesia (KBI). This study aims to examine the socio-economic factors that influence the income distribution gap in KTI, with a focus on economic growth, employment opportunities, farmer exchange rates, regional minimum wages, and education. Quantitative analysis tools used are panel data regression models with fixed effect model estimation techniques. The data used is panel data of 12 provinces in Eastern Indonesia, for the period 2010-2017. The results showed that both partially and simultaneously economic growth, employment opportunities, farmer exchange rates, and education levels contributed significantly to reducing the income distribution gap. The recommendation for regional governments is to accelerate economic growth accompanied by the expansion of employment opportunities and education development equally, and also the optimization of agricultural sector development.